An insect farnesyl phosphatase homologous to the N-terminal domain of soluble epoxide hydrolase - Cao, Li (2009)
In insects, farnesyl pyrophosphate (FPP) is converted to juvenile hormone (JH) via a conserved pathway consisting of isoprenoid derived metabolites. The first step of this pathway is presumed to be hydrolysis of FPP to farnesol in the ring gland. Based on alignment of putative phosphatases from D. melanogaster with the phosphatase domain of soluble epoxide hydrolase, Phos2680 and Phos15739 with conserved phosphatase motifs were identified, cloned and purified. Both D. melanogaster phosphatases hydrolyzed para-nitrophenyl phosphate, however, Phos15739 also hydrolyzed FPP with a Kcat/Km of 2.1 X 10(5) M(−1)s(−1). RT-PCR analysis revealed that Phos15739 was expressed in the ring gland and its expression was correlated with JHIII titer during development of D. melanogaster. N-acetyl-S-geranylgeranyl-L-cysteine was found to be a potent inhibitor of Phos15739 with an IC(50) value of 4.4 μM. Thus, our data identify Phos15739 as a FPP phosphatase that likely catalyzes the hydrolysis of FPP to farnesol in D. melanogaster.